Influences of dissolved oxygen sensor position on aeration efficiency of Venturi air injectors in aquaculture and wastewater treatment - Nantawat, Demeekul; Puangsuwan, Kritsada; Eknarin, Rodcharoen; Kuaanan, Techato; Anil, Kumar (International Journal of Agricultural and Biological Engineering, 2025)
This article concentrates on the aeration efficiency of venturi air injectors in aquaculture or wastewater treatment. This study was designed to investigate the location of the dissolved oxygen (DO) sensor installation, with a focus on investigating the aeration mechanism by studying ten variables, including temperature, pH, oxidation-reduction potential (ORP), electrical conductivity, resistivity, total dissolved solids, salinity, pressure, dissolved oxygen, and the effect of changing the position of DO sensor installations in different locations via oxygen transfer. The water temperature was raised due to the heating of the water pump. It ranged from 29.7°C to 32.78°C, with different temperatures resulting in different oxygen solubility. The pH level increased with the rise in oxygen levels due to an increase in OH– concentration, whereas the ORP decreased when oxygen levels rose, increasing the reduction reaction. A study on the effect of changing the position of DO sensor installations in different locations was discovered using oxygen transfer coefficients (KLa) variables. The KLa values at nozzle depths of 15 cm, 30 cm, and 45 cm were 0.0004±0.0001, 0.000 42±0.0001, and 0.001 36±0.000 13, respectively. Therefore, there is a slight difference of KLa value when changing the position of sensor installations. An inappropriate distance between the DO sensor and nozzle installation is able to cause turbulent flow. This event resulted in an incorrect DO value. Moreover, the installation of the DO sensor too far from the nozzle resulted in a low value of DO. Keywords: venturi aspirator, aeration systems, aeration efficiency, dissolved oxygen, position of DO sensor, DO sensor DOI: 10.25165/j.ijabe.20251803.8962 Citation: Demeekul N, Puangsuwan K, Rodcharoen E, Techato K, Kumar A. Influences of dissolved oxygen sensor position on aeration efficiency of Venturi air injectors in aquaculture and wastewater treatment. Int J Agric & Biol Eng, 2025; 18(3):58–62.